Orthographic Transparency of Rote Speech Varieties: Challenges in Language Learning - Thersia Magdalena Tamelan; Dendi Wijaya; Festif Rudolf Hoinbala; I Gusti Ayu Gde Sosiowati (Masyarakat Linguistik Indonesia, 2026)
Effective orthographic systems are essential for language documentation and revitalization. This study examines the orthographic transparency of six Rote speech varieties—Dela, Dengka, Tii, Lole, Termanu, and Rikou—focusing on the consistency of sound–symbol correspondences and their implications for language learning. Data were collected from published materials, field observations, and interviews with native speakers. The findings reveal inconsistencies in the representation of implosive consonants (/ɓ/, /ɗ/), the glottal stop (/ʔ/), and double vowels. These inconsistencies reduce orthographic transparency, hinder learnability, and disrupt grapheme–phoneme correspondences. The study highlights the importance of transparent and consistent orthographic representation for literacy development and language revitalization. It proposes recommendations for improving orthographic transparency across Rote speech varieties.